2018
DOI: 10.1158/1078-0432.ccr-17-0691
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Production by Myeloid-Derived Suppressor Cells Plays a Role in Impairing Fc Receptor–Mediated Natural Killer Cell Function

Abstract: mAbs are used to treat solid and hematologic malignancies and work in part through Fc receptors (FcRs) on natural killer cells (NK). However, FcR-mediated functions of NK cells from patients with cancer are significantly impaired. Identifying the mechanisms of this dysfunction and impaired response to mAb therapy could lead to combination therapies and enhance mAb therapy. Cocultures of autologous NK cells and MDSC from patients with cancer were used to study the effect of myeloid-derived suppressor cells (MDS… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 194 publications
(151 citation statements)
references
References 59 publications
3
128
1
2
Order By: Relevance
“…This suppression of natural killer cells is cell-cell contact-dependent. [70][71][72][73][74][75][76] Therefore, MDSCs exert a wide range of immunosuppressive functions across the immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…This suppression of natural killer cells is cell-cell contact-dependent. [70][71][72][73][74][75][76] Therefore, MDSCs exert a wide range of immunosuppressive functions across the immune systems.…”
Section: Discussionmentioning
confidence: 99%
“…Other cell types of the innate and adaptive immune systems, which are susceptible to MDSC-mediated suppression of protective functions include natural killer (NK) cells and B cells, and this is also achieved via contact-dependent and -independent mechanisms involving ROS, NO, arginase and TGFβ1 [65,110].…”
Section: Other Mechanismsmentioning
confidence: 99%
“…The result of studies demonstrated that MDSCs impair NK cell ADCC function through production of nitric oxide (NO). In addition, the expression of immunosuppressive inhibitory adenosine A2A receptors (A2ARs) by MDSCs in tumor sites signals to inhibit the activity of NK‐cells (Cekic, Day, Sag, & Linden, ; Stiff et al, ). Other study revealed that NK cells attenuated by MDSCs through the inhibiting of IFN‐γ production and NKG2D in glioma cells (Alizadeh et al, ).…”
Section: Nk Cells In Hematological Malignanciesmentioning
confidence: 99%